Estimation of NERICA adoption Rates and Impact on Productivity and Poverty of the Small-Scale Rice Farmers in The Gambia - Dibba, Lamin (2011)
Thesis submitted to the Faculty of Agriculture, Department of Agricultural Economics, Agri-business and Extension in Partial Fulfilment of the Requirements for the degree of Master of Philosophy in Agricultural Economics April.